Development and Use of a Planter for Simultaneous Application of Seed, Fertilizer and Compost in Pearl Millet Production in Niger—Effects on Labor Use, Yield and Economic Return - Abdourahamane Issa M. Nourou; Addam Kiari Saidou; Jens B. Aune (Agronomy, 2020)
Sowing and application of mineral and organic fertilizer is generally done manually in the Sahel, resulting in low precision and delayed application. The objective of this paper is to present a new mechanical planter (Gangaria) for the combined application of seeds and soil amendments (mineral fertilizer, compost, etc.), and to assess the effects of using this planter in pearl millet on labor use, yield and economic return. The labor study showed that the mechanized application of seeds and compost reduced time use by a factor of more than six. The on-station experiments were completely randomized experiments with six replications and six treatments: T0 (control), T1 (0.3 g NPK hill−1), T2 (25 g compost hill−1), T3 (25 g compost + 0.3 g NPK hill−1), T4 (50 g compost hill−1) and T5 (50 g compost + 0.3 g NPK hill−1). Treatments T1 to T5 were sown by the planter with seeds that were primed in combination with coating of seeds with a fungicide/insecticide. The treatment T5 increased grain yield and economic return compared to the control by 113% and 106%, respectively. The advantages for farmers using this approach of agricultural intensification are timelier sowing of dryland cereal crops, easy application of organic fertilizer and more precise delivery of input, thereby making this cropping system more productive and less vulnerable to drought.